Le sorgho - Chantereau, Jacques (éditions Quae, 2013)
Sorghum is a vital food crop for populations in arid and sub-arid areas. It is also cultivated in temperate areas for animal feed. This book addresses all aspects of the plant (biology, genetics, sensitivity to pests) together with the cultivation systems, harvesting methods and how it is processed into human food. A wealth of illustrations supplement the in-depth, up-to-date knowledge on sorghum, its ecological functions and integrated protection.